Vocational High School Students’ Views on English Subject for Their Current Knowledge and Future Career - Monalisa Gabriella Risanti; Reyssa Aurora Carolina; Akhmad Fauzan; Emeral Emeral (Journey: Journal of English Language and Pedagogy, 2025)
Vocational High School (SMK) is one of the most popular choices for students in Indonesia due to its focus on work preparation for students. Therefore, students need to be equipped with knowledge and abilities that are relevant to their department. To fulfill this, all subjects, including English, are designed to support their knowledge in their future field of work. In this case, the researchers examined student perceptions towards English General Purposes (EGP) and English for Specific Purposes (ESP) as well as the methods applied by teachers in ESP learning. In addition, this study also analyzed students’ aspirations related to their study program or outside the study program. This research employed quantitative approach. The Participant of this research was 102 students from class XI of Skin and Hair Beauty Department and also XI Fashion Design and Production Department of SMK Negeri 3 Palangka Raya. The results show that students agree that EGP (67.36%) and ESP (74.93%) can support their future careers. This is also supported by the ESP learning method from teachers at 75.65%. For career aspirations, 50.73% of VHS students have career aspirations related to their study program. While 56.72% have career aspirations outside their study program.